The Effect of Wordwall Media Integration in Linear Program Learning on Students' Concept Understanding and Learning Interest - Marta Uli Pasaribu; Amin Harahap; Lily Rohanita Hasibuan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This research seeks to evaluate the impact of integrating Wordwall media on students' enthusiasm for learning and grasp of mathematical principles in linear programming topics. A lack of interest and challenges in comprehending abstract mathematical ideas serve as the foundation for this investigation. Wordwall was selected due to its provision of interactive learning experiences that enhance student participation. The research adopted a quasi-experimental approach using a non-equivalent control group design. The tools for research included a concept comprehension test (15 questions) and a learning interest survey (30 statements). Data analysis involved the Kolmogorov-Smirnov normality check, Levene's homogeneity examination, paired sample t-test, independent sample t-test, and N-Gain. The findings revealed that the incorporation of Wordwall media significantly and positively influenced students' enthusiasm for learning and their comprehension of mathematical concepts. The progress noted in the experimental group was classified as moderate, while the control group exhibited relatively minimal improvement. Consequently, Wordwall media can serve as a viable alternative learning tool to elevate the quality of mathematics education in vocational high schools. In conclusion, this study asserts that the incorporation of Wordwall media is effective in boosting students' enthusiasm for learning and their understanding of mathematical principles.